A comprehensive diagnosis of a desmoplastic small round cell tumor of unusual location based on fine‐needle aspiration cytology: Report of a case arising in the parotid gland and review of the literature. Issue 9 (13th July 2020) - Lozano, María D.; Landa, Ana; Tobar, Laura G.; De Andrea, Carlos; Larrache, Javier; Echeveste, Jose I.; Paricio, Jose J.; Sánchez, Beatriz; Medina, Andrea; Paisan, Ana
Abstract: Desmoplastic small round cell tumor (DSRCT) is rare and a highly aggressive neoplasm that typically involves the soft tissues of the abdomen or pelvis in children or young adults, showing a male predilection. Although it can occurs over a wide age range, the peak incidence is in the third decade of life. DSRCT usually shows widespread abdominal serosal involvement, and overall patient survival is poor. On the other hand, extra‐abdominal DSRCT is very rare. DSRCT in major salivary glands has been reported, but it is extremely rare. In the majority of reported series diagnosis is made by the histological analysis of FFPE tissues together with immunohistochemistry (IHC) and molecular analysis, particularly the demonstration of chromosomal translocation involving EWSR1. Very few cases have been diagnosed so far by Fine Needle Aspiration (FNA) cytology. Moreover ancillary studies have been performed in all reported cases in FFPE samples. There is still controversy and lack of consensus regarding the suitability of cytological samples especially smears for immunocytochemical (ICC) and fluorescence in situ hybridization (FISH), what makes its standardization difficult. We report a case of a primary DSRCT of parotid gland in a 17‐year‐old male diagnosed by FNA cytology. The cytomorphological diagnosis was coupled with ICC and FISH analysis performed on stained smears. We emphasize the feasibility and reliability of cytological smears for the application of immunocytochemical and molecular techniques.